1996
DOI: 10.1016/0165-0114(95)00165-4
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy multiple criteria decision making: Recent developments

Abstract: Multiple Criteria Decision Making (MCDM) shows signs of becoming a maturing field. There are four quite distinct families of methods: (i) the outranking, (ii) the value and utility theory based, (iii) the multiple objective programming, and (iv) group decision and negotiation theory based methods. Fuzzy MCDM has basically been developed along the same lines, although with the help of fuzzy set theory a number of innovations have been made possible; the most important methods are reviewed and a novel approach -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
138
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(147 citation statements)
references
References 93 publications
0
138
0
9
Order By: Relevance
“…Many different MCDA approaches are presented and categorised in (Belton and Stewart, 2003;Carlsson and Fullér, 1996;Chen et al, 1992;Kahraman, 2008;Triantaphyllou, 2000). Instead of focusing of separate MCDA methods, we will first look at the major families of MCDA methods.…”
Section: Choice Of Mcda Approachmentioning
confidence: 99%
“…Many different MCDA approaches are presented and categorised in (Belton and Stewart, 2003;Carlsson and Fullér, 1996;Chen et al, 1992;Kahraman, 2008;Triantaphyllou, 2000). Instead of focusing of separate MCDA methods, we will first look at the major families of MCDA methods.…”
Section: Choice Of Mcda Approachmentioning
confidence: 99%
“…In fact, the total goal is to select an alternative with the best tradeoff between all goals. To evaluate the concepts like dominance, similarity, and contrast between different alternatives, some criteria can be defined [6]. The fuzzy set theory has been used widely in decision making problems.…”
Section: Proposed Dpm Systemmentioning
confidence: 99%
“…A review and comparison of many of these methods can be found in [2], [4], [5] and [6]. Abdullah [7] presents a brief review of category in fuzzy multi criteria decision making and describes some of its earliest and recent applications.…”
Section: Introductionmentioning
confidence: 99%